The Modulation of Interferon Regulatory Factor-1 via Caspase-1-Mediated Alveolar Macrophage Pyroptosis in Ventilator-Induced Lung Injury - Minhui Dai; Qian Li; Pinhua Pan (Hindawi Limited, 2022)
Background. To examine the role of interferon regulatory factor-1 (IRF-1) and to explore the potential molecular mechanism in ventilator-induced lung injury. Methods. Wild-type C57BL/6 mice and IRF-1 gene knockout mice/caspase-1 knockout mice were mechanically ventilated with a high tidal volume to establish a ventilator-related lung injury model. The supernatant of the alveolar lavage solution and the lung tissues of these mice were collected. The degree of lung injury was examined by hematoxylin and eosin staining. The protein and mRNA expression levels of IRF-1, caspase-1 (p10), and interleukin (IL)-1β (p17) in lung tissues were measured by western blot and quantitative real-time polymerase chain reaction, respectively. Pyroptosis of alveolar macrophages was detected by flow cytometry and western blotting for active caspase-1 and cleaved GSDMD. An enzyme-linked immunosorbent assay was used to measure the levels of IL-1β, IL-18, IL-6, TNF-α, and high mobility group box protein 1 (HMGB-1) in alveolar lavage fluid. Results. IRF-1 expression and caspase-1-dependent pyroptosis in lung tissues of wild-type mice were significantly upregulated after mechanical ventilation with a high tidal volume. The degree of ventilator-related lung injury in IRF-1 gene knockout mice and caspase-1 knockout mice was significantly improved compared to that in wild-type mice, and the levels of GSDMD, IL-1β, IL-18, IL-6, and HMGB-1 in alveolar lavage solution were significantly reduced (P<0.05). The expression levels of caspase-1 (p10), cleaved GSDMD, and IL-1β (p17) proteins in lung tissues of IRF-1 knockout mice with ventilator-related lung injury were significantly lower than those of wild-type mice, and the level of pyroptosis of macrophages in alveolar lavage solution was significantly reduced. Conclusions. IRF-1 may aggravate ventilator-induced lung injury by regulating the activation of caspase-1 and the focal death of alveolar macrophages.